(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
ABSTRACT: In most countries of the world, language use in any society is distinguishable and it is based on certain sociological parameters. The present paper thus attempts to examine language codes in social class and language prestige in order to reveal language use in relation to societal classes. It also casts light on monolingualism and bilingualism in order to unveil the differences in various sociolinguistic settings. Moreover, it examines the main distinctions between the concepts of diglossia and polyglottism. It studies language contact, multilingualism, and characteristics and types of multilinguals in order to understand these phenomena in sociolinguistics. The current paper comes to show the links between language and social interaction, and language and action in order to understand the perception of language use in interaction. KEYWORDS: language use, society, monolingualism, bilingualism, diglossia, polyglottism. ملخص: يمكن تحديد استخدام اللغة في أي مجتمع في العالم ويستند هذا إلى معايير اجتماعية معينة. و لهذا تحاول هذه الورقة البحثية دراسة رموز اللغة في الطبقة الاجتماعية وهيبتها من أجل الكشف عن الاستخدام اللغوي فيما يتعلق بالطبقات المجتمعية و كما تلقي الضوء أيضاً على ظاهرتي أحادية اللغة وثنائية اللغة لإبراز الاختلافات الموجودة في مختلف البيئات اللغوية الاجتماعية. علاوة على ذلك، تبحث هاته الدراسة في الفروق الرئيسة بين مفاهيم ازدواجية اللغة و تعدد اللغات، كما تدرس الاتصال اللغوي و خصائص و أنواع تعدد اللغات و هذا من أجل فهم هذه الظواهر في علم اللغة الاجتماعي. و تأتي الورقة الحالية لإظهار الروابط بين اللغة والتواصل الاجتماعي، واللغة و الأداء من أجل استيعاب كيفية استخدام اللغة في التواصل. كلمات دالة: استخدام اللغة، المجتمع، أحادية اللغة، ثنائية اللغة، ازدواجية اللغات، تعدد اللغات.